1986
DOI: 10.1002/pssa.2210950228
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced diffusion phenomena during rapid thermal annealing of preamorphized boron-implanted silicon

Abstract: The diffusion of boron implanted in preamorphized silicon and rapid thermal annealed with an electron beam is analyzed. For an implanted dose of 5× 1015 B+/cm2 an enhanced diffusion in the early phase of the annealing is clearly observed. The enhancementof the diffusivity is of about a factor 30 at t  0 and exponentially decreases with a constant time of 0.5 s at the temperature of 1100 °C. For lower implanted dose (1 × 1015 B+/cm2) the phenomenon is less remarkable and no conclusive evidence on the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In these previous studies, the EB resist used was poly(glycidyl methacrylate) (PGMA) which had high sensitivity but low dry etch resistance. On the other hand, polystyrene type EB resists such as chlorinated polymethylstyrene (CPMS) (6)(7)(8), chloromethylated polystyrene (CMS) (9,10), and iodinated polystyrene (IPS) (11) have been known as dry etch resistant EB resists. This paper reports EB exposure characteristics of highly sensitized CMS, and dry etching processes of mask fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these previous studies, the EB resist used was poly(glycidyl methacrylate) (PGMA) which had high sensitivity but low dry etch resistance. On the other hand, polystyrene type EB resists such as chlorinated polymethylstyrene (CPMS) (6)(7)(8), chloromethylated polystyrene (CMS) (9,10), and iodinated polystyrene (IPS) (11) have been known as dry etch resistant EB resists. This paper reports EB exposure characteristics of highly sensitized CMS, and dry etching processes of mask fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, only a theoretical approach of the kinetics involved in the process can be helpful to describe the experimental results. Several authors (2,5,8,9,12) have in fact simulated the evolution of the doping profiles by hypothesizing an exponential decay with time of the enhanced diffusion coefficient.In this work investigations on B, P, As, and Sb diffusivities were made also at low temperature, and the time dependence of the diffusion coefficient D was accurately determined in the B case. The results show that D is nearly constant until a time value is reached which diminishes with the annealing temperature, beyond which it tends asymptotically to the equilibrium value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of activation by a nonthermal equilibrium state, impurities beyond the solubility limit of Si will be incorporated. 30) Impurities beyond the solubility limit of Si will be released from lattices with increasing annealing temperature and annealing time, and eventually the concentration returns to a value at the solubility limit. 31) As in double-pulse irradiation, activation by a nonthermal equilibrium state also occurs.…”
Section: Cross-sectional Tem Observation Of Crystallinity and Contact...mentioning
confidence: 99%
“…Usually, in recrystallization from an amorphous layer, solid phase growth is induced by low-temperature annealing at about 500 °C or lower, and impurities with the solubility limit higher than that of Si will be incorporated. 38) In addition, the impurities beyond the solubility limit in Si will be released from the lattice position with increasing annealing temperature and passage of annealing time, and eventually the concentration returns to the solubility limit. 39) From these results, it is shown that the crystallized state of the amorphous layer formed by cryogenic Ge implantation clearly differs from that formed by room-temperature and cryogenic B implantations.…”
Section: Crystal Structure Analysis Based On Rbs and Pn Junction Leak...mentioning
confidence: 99%